Artificial intelligence technologies and related urban planning and development concepts: How are they perceived and utilized in Australia? - Tan Yigitcanlar; Nayomi Kankanamge; Massimo Regona; Andres Ruiz Maldonado; Bridget Rowan; Alex Ryu; Kevin C. Desouza; Juan Manuel Corchado; Rashid Mehmood; Rita Yi Man Li (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Artificial intelligence (AI) is a powerful technology with an increasing popularity and applications in areas ranging from marketing to banking and finance, from agriculture to healthcare and security, from space exploration to robotics and transport, and from chatbots to artificial creativity and manufacturing. Although many of these areas closely relate to the urban context, there is limited understanding of the trending AI technologies and their application areas-or concepts-in the urban planning and development fields. Similarly, there is a knowledge gap in how the public perceives AI technologies, their application areas, and the AI-related policies and practices of our cities. This study aims to advance our understanding of the relationship between the key AI technologies (n = 15) and their key application areas (n = 16) in urban planning and development. To this end, this study examines public perceptions of how AI technologies and their application areas in urban planning and development are perceived and utilized in the testbed case study of Australian states and territories. The methodological approach of this study employs the social media analytics method, and conducts sentiment and content analyses of location-based Twitter messages (n = 11,236) from Australia. The results disclose that: (a) digital transformation, innovation, and sustainability are the most popular AI application areas in urban planning and development; (b) drones, automation, robotics, and big data are the most popular AI technologies utilized in urban planning and development, and; (c) achieving the digital transformation and sustainability of cities through the use of AI technologies-such as big data, automation and robotics-is the central community discussion topic.
Keywords: 650; sustainability; artificial intelligence (AI); Australia; automation; big data; digital transformation; innovation; public perception; robotics; urban planning and development